Anonymous and authenticated routing protocol for mobile ad hoc networks - LI Xiao-qing; LI Hui; MA Jan-feng (Tongxin xuebao)
Aimed at the anonymous of open environment of mobile ad hoc networks was not considered in the routing protocol of ARAN, and it was a low efficiency protocol in searching a routing.An new anonymous and authenticated routing protocol for mobile ad hoc networks（AARAN） was presented, It made use of hash function, signature and Hello message.The protocol can effectively ensure the anonymous of the networks, avoid launching a routing request repeat-edly, so it improves the efficiency, and the protocol can availably account for the harm which is caused by selfish nodes.